2015
DOI: 10.4028/www.scientific.net/amm.752-753.163
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the Influence of a Pointed Field Emission Cathode Design from the Silicon Carbide with Graphene Film on the Electric Field Strength

Abstract: Graphene film on silicon carbide is considered to be promising material for high-frequency vacuum nanoelectronics. However, the possibility of graphene application in this area is still poorly understood. We have carried out the simulation of the electric field distribution in interelectrode gap of the anode-cathode system pointed field emission cathode based on silicon carbide with graphene film on its surface subject to the rounding-off radius of the top, interelectrode gap, height and cathode forming half-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The cathodes in the shape of the tip, the blade and matrix structures are of the greatest interest. Previously, it was found that interelectrode spacing and rounding-off radius of the top having the greatest impact on the electric field strength [17]. It was determined that achievement of a field strength 10 9 V/m in nanoscale field emission structures is possible at a potential difference of less than 10 V. The small size of field emission cathode allows to create a compact matrix structure with a high current density [18].…”
Section: Designmentioning
confidence: 99%
“…The cathodes in the shape of the tip, the blade and matrix structures are of the greatest interest. Previously, it was found that interelectrode spacing and rounding-off radius of the top having the greatest impact on the electric field strength [17]. It was determined that achievement of a field strength 10 9 V/m in nanoscale field emission structures is possible at a potential difference of less than 10 V. The small size of field emission cathode allows to create a compact matrix structure with a high current density [18].…”
Section: Designmentioning
confidence: 99%